Custodial patrimony and its contradictions: prisons as patrimonies in France in present time - Borges, Viviane Trindade (2018)
This article focuses on struggles in practices of prisons as patrimonies in France. By approaching Prison de La Santé’s case, open to public visit during the Patrimony Symposium in 2014, we intend to make clear the discussion and some theoretical and methodological implications as part of a concept construction – prison patrimony – which has been increasingly controversial in France in the last ten years. We analyze the questionable functions of some prisons of the XIXth Century still in operation and/or disabled, monumental buildings made obsolete nowadays and marked by struggles in controversial actions for creating patrimonies, as well as we approach deeply some historians’s roles in this process.